Analisis Pola Komunikasi dalam Hubungan Percintaan Pada Generasi Milenial - Suryani, Irma; Al Farizi, Muhammad; Fadhilah, Meirah; Rismayani, Rismayani; Nabia, Wasiatul; Yusdarly, Yusdarly; Rahmaliza, Rahmaliza (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This article discusses the role of communication in human life, focusing on millennials' communication patterns in romantic relationships. Communication is considered a fundamental element that shapes social interactions and relationships between individuals. Millennials, living in the digital age, exhibit fast and instant communication patterns, often through social media and text messages. Although technology makes interactions easier, new challenges arise such as a lack of interpersonal communication skills. This research uses a literature review approach to analyze the communication patterns of millennials, as well as the positive and negative impacts of using technology in relationships. Hopefully, by understanding these communication patterns, more effective strategies can be found to improve the quality of millennials' romantic relationships.